Day admission for thoracic aortic surgery - Silvay, G (EDIMES Edizioni Internazionali Srl, 2010)
Elective cardiac surgical patients can be admitted on the morning of the operation. The day admission surgery is safe with optimal care for patients and provides an economical benefit. In our institution if immediate surgery is not required, patients are entered into program for serial follow up. An elective aortic intervention for open surgical or endovascular surgery is recommended when the risk of aortic rupture outweighs the risk of surgery. Patients are seen 3 to 7 days prior of day admission surgery in preoperative clinic. On the morning of surgery, the patient undergoes a reassessment to ensure no interval changes have occurred. We hereby describe our three years experience with 350 patients were referred from the Aortic Aneurysm Surveillance Program. We believe that not only patients, but all medical personal benefit from a complete preoperative evaluation of these complicated patients and this creates harmony during the entire hospitalization!